Human augmentation: Past, present and future - Raisamo, Roope; Rakkolainen, Ismo; Majaranta, Päivi; Salminen, Katri; Rantala, Jussi; Farooq, Ahmed (International journal of human-computer studies, 2019)
•Human augmentation will change what it means to be human.•A definition and model for human augmentation are presented.•Physical and digitally mediated actions can be combined to extend human reach.•Non-invasive augmentation is possible with augmented reality and wearable technology.•A call for research is presented to realize the vision of human augmentation. Human augmentation is a field of research that aims to enhance human abilities through medicine or technology. This has historically been achieved by consuming chemical substances that improve a selected ability or by installing implants which require medical operations. Both of these methods of augmentation can be invasive. Augmented abilities have also been achieved with external tools, such as eyeglasses, binoculars, microscopes or highly sensitive microphones. Lately, augmented reality and multimodal interaction technologies have enabled non-invasive ways to augment human. In this article, we first discuss the field and related terms. We provide relevant definitions based on the present understanding of the field. This is followed by a summary of existing work in augmented senses, action, and cognition. Our contribution to the future includes a model for wearable augmentation. In addition, we present a call for research to realize this vision. Then, we discuss future human abilities. Wearable technologies may act as mediators for human augmentation, in the same manner as eyeglasses once revolutionized human vision. Non-invasive and easy-to-use wearable extensions will enable lengthening the active life for aging citizens or supporting the full inclusion of people with special needs in society, but there are also potential problems. Therefore, we conclude by discussing ethical and societal issues: privacy, social manipulation, autonomy and side effects, accessibility, safety and balance, and unpredictable future.